Influence of sea mud state on the anodic behavior of Al-Zn-In-Mg-Ti sacrificial anode. (15th May 2017) - Wan, Hongxia; Huangfu, Wenzhu; Liu, Zhiyong; Du, Cuiwei; Li, Xiaogang; Song, Dongdong; Cao, Bei
Abstract: The influence of sea mud state on the anodic behavior of Al-Zn-In-Mg-Ti sacrificial anode was investigated by the methods of electrochemical, immersion and surface analysis techniques. In this work, the simulated seawater, sea mud and seawater/sea mud transition region systems were set up in laboratory, it can measure the galvanic corrosion of sacrificial anode in seawater/sea mud transition environment. Results show that the corrosion rate of Al-Zn-In-Mg-Ti sacrificial anode in simulated seawater is higher than that in simulated sea mud. And the corrosion rate increased with the increasing size of sea mud. When the Al-Zn-In-Mg-Ti sacrificial anode and Q235 joint together at the ratio of cathode and anode area of 50:1, the mix potential shift negative with the increasing size of sea mud and the mixed current density is highest in seawater and increase with the increasing size of sea mud. The corrosion rate is determined by the conductivity and dissolved oxygen in various mud size. In simulated seawater environment, Al-Zn-In-Mg-Ti sacrificial anode present relatively uniform dissolution; however, in simulated sea mud environment, due to the different dissolved oxygen in various mud size, Al-Zn-In-Mg-Ti sacrificial anode present nonuniform dissolving, especially in simulated lager particles sea mud. Highlights: A device was set up to study galvanic corrosion of sacrificial anode in sea mud and sea water. Influence of sea mud state on anodic behavior of Al-Zn-In-Mg-Ti is investigated. The mix potential and current density were measured when Al-Zn-In-Mg-Ti and Q235 joint together. Propose different corrosion types in seawater and sea mud environment.